Fundamental of Entrepreneurship ENT300 : Captain Shrimp / Nur Fatihahtul Amirah Abdul Rahim ... [et al.] - Abdul Rahim, Nur Fatihahtul Amirah; Ismail, Nurul Izzah; Ahmad, Rahida (2019)
Supplying fresh shrimp straight from the pond may build and increase the consumers trust on the quality of shrimp. We are providing something worth for them. The management of shrimp pond is quite tough but we would like to take the challenges in order to have best quality output. The shrimp is high in several vitamins and minerals, and also rich of protein. People nowadays are having high in demand of shrimp especially for the food court. Therefore, we are here to solve the problem which is by providing the fresh and better quality of shrimps that is based in Mukah. We will first come up with the business plan beforehand. In this business plan, there are organized strategies and plans for our business. The area of our targeted selling business is Mukah since this area is in the process of developing into a tourist destination. People would know Mukah as an area with selling a lot of fresh seafood because it has a lot of fishermen. They usually fishing fresh seafood and then sell them at Pasar Ikan Mukah, which is the place with a lot of potential consumer. Other than that, mere are a lot of growing restaurant in Mukah which provide sea food that is quite tasty. These restaurants would need a supplier of fresh seafood but then, there is only a little number of suppliers in Mukah. Therefore, we have come up with the business idea of supplying one of fresh seafood, which is shrimp. The business name would be Captain Shrimp. We will provide fresh shrimp from the better management. We will sell only the better quality of shrimp. The shrimp is chosen among the rest of seafood because in Mukah, the demand of the shrimp is higher. Not only that, there are mostly existed of fish supplier in Mukah. We wanted to give the reasonable price for fresh shrimp to potential consumer and make them view us as the trusted supplier.